Implikasi pasal 7 ayat (1) keputusan menteri perindustrian dan perdagangan nomor 651/mpp/kep/10/2004 terhadap praktik penjualan air galon isi ulang di toko eceran: Studi kasus depot air isi ulang oranye - Nugraheni, Septya Dwi; Hasan, Akhmad Farroh (Maliki Interdisciplinary Journal, 2025)
Water is a fundamental human need that plays a vital role in supporting daily activities and maintaining bodily fluid balance. As public awareness of the importance of hygienic drinking water increases, the bottled drinking water industry (AMDK) has experienced significant growth, including the emergence of refillable drinking water depots (DAMIU). Refilled water is considered a practical, economical, and efficient alternative to branded bottled water. In Mojokerto, the penetration of DAMIU is relatively high, driven by affordable pricing and ease of distribution. However, alongside its development, legal issues have arisen regarding distribution practices that violate Article 7 paragraph (1) of the Decree of the Minister of Industry and Trade No. 651/MPP/Kep/10/2004, which mandates that sales be conducted directly to consumers at the depot location. This study examines the practices of DAMIU in Mojokerto, particularly the Oranye Refill Depot, to assess compliance with applicable regulations and explore the legal implications. The research aims to provide insights into the legal responsibilities of business operators in the event of violations and contribute to the development of legal policies regarding refill water distribution in Indonesia. This study uses a normative-juridical method with a statutory and field case study approach. It also emphasizes the importance of legal enforcement for non-compliant business actors to ensure consumer protection and legal certainty. Furthermore, the results of this study are expected to serve as a reference for the government in supervising and guiding DAMIU operations.